In chains for my country : crusading for the British Southern Cameroons - Nfor, N. Nfor (Langaa Research & Publishing CIG, 2014)
In Chains for My Country is an account of the struggle of the Southern Cameroons National Council (SCNC), a nonviolent liberation movement, to wrestle British Southern Cameroons from the colonial claws of la Republique du Cameroun. It is an epic and thrilling account of the life of British Southern Cameroons, which passed from colonial rule to foreign domination through annexation and attempted assimilation into neighbouring la Republique du Cameroun. Under British trusteeship, British Southern Cameroons graduated to self-government in 1954 with all hopes of independence. Instead, the Trust Territory was doomed to subservience in a contested union with la Republique du Cameroun. Failure to implement United Nations Resolution 1608 of April 1961 to establish the envisioned federation of two states equal in status facilitated la Republique du Cameroun's annexation and colonial occupation of a defenseless United Nations Trust as Britain withdrew all its personnel and forces. The territory has been reduced to two provinces of la Republique du Cameroun under the rule of proconsuls backed by an imperial occupation force with an agenda of nipping in the bud any resistance.